2007
DOI: 10.1021/jf071563y
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Evaluation of Struvite and Sludges from Municipal Wastewater Treatment Works as Phosphorus Sources for Plants

Abstract: Sewage sludge obtained by a conventional aerobic activated sludge process (CSS), P-rich sewage sludge from an enhanced biological P removal process (PRS), and struvite (MgNH 4PO 4 x 6H 2O) recovered from an anaerobic digester supernatant using a low-grade MgO byproduct from the calcination of natural magnesite as a Mg source (STR) were evaluated as P sources for plant growth. For this purpose, a greenhouse pot experiment was conducted using a P-deficient loamy sand soil and perennial ryegrass ( Lolium perenne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
61
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 37 publications
7
61
0
6
Order By: Relevance
“…These results corroborate findings from numerous other studies that demonstrated various recovered struvite products to be of similar effectiveness to commercial P fertilizers for yields of spring wheat (Massey et al, 2009), corn (Barak and Stafford, 2006;Gell et al, 2011), and ryegrass (Antonini et al, 2012;Johnston and Richards, 2003;Plaza et al, 2007). In contrast, Ackerman et al (2013) reported lower canola DMY and P Cs ´ S <0.001 0.22 † Two-, three-, four-, and five-way interactions with P > 0.1 for both parameters are not presented.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results corroborate findings from numerous other studies that demonstrated various recovered struvite products to be of similar effectiveness to commercial P fertilizers for yields of spring wheat (Massey et al, 2009), corn (Barak and Stafford, 2006;Gell et al, 2011), and ryegrass (Antonini et al, 2012;Johnston and Richards, 2003;Plaza et al, 2007). In contrast, Ackerman et al (2013) reported lower canola DMY and P Cs ´ S <0.001 0.22 † Two-, three-, four-, and five-way interactions with P > 0.1 for both parameters are not presented.…”
Section: Discussionsupporting
confidence: 90%
“…In a greenhouse experiment using Italian ryegrass (Lolium multiflorum L.) and corn, DMY and P uptake from various urine-and manure-recovered struvites equaled or exceeded those for Cederan phosphate fertilizer (Antonini et al, 2012). Plaza et al (2007) reported that struvite recovered from an anaerobic digester supernatant was as effective as single superphosphate at increasing DMY and supplying P to perennial ryegrass. Similarly, wastewater-derived struvites gave spring wheat DMY similar to triple superphosphate fertilizer in slightly acidic (pH 6.5) and alkaline (pH 7.6) soils (Massey et al, 2009).…”
mentioning
confidence: 99%
“…It is known that water-soluble P fertilizer is generally considered to be fully plant available, and the P uptake from struvite has been studied in the greenhouse with a variety of test plants on soils compared with commercial P fertilizer. [8][9][10][11] evaluated the availability of urine-derived struvite as fertilizer and found that struvite led to biomass yield and P uptake comparable to or higher than those induced by a commercial mineral fertilizer. A few reports of the comparison of soils with different pH values can be found in previous research.…”
mentioning
confidence: 99%
“…The solubility of pure MAP is considered to be low, 0.23 g L -1 , compared with about 18 g L -1 for Ca(H 2 PO 4 ) 2 (Weast 1970). In spite of this low solubility several studies have found that struvite from sewage sludge is as effective as water-soluble P fertilizers in alkaline, neutral and slightly acid soils (Johnston and Richards 2003;Plaza et al 2007;Massey et al 2009). This shows that in spite of the low solubility of MAP, the soil provides conditions that favour its solubilization.…”
mentioning
confidence: 99%